On classification of pairs of potent linear operators with the simplest annihilation condition - Bondarenko, V.M.; Tertychna, O.M.; Zubaruk, O.V. (Algebra and Discrete Mathematics, 2016)
We study the problem of classifying the pairs of linear operators A,B (acting on the same vector space), when the both operators are potent and AB=0. We describe the finite, tame and wild cases and classify the indecomposable pairs of operators in the first two of them.